2007
DOI: 10.1016/j.jmb.2007.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Disabled-1 Tyrosine Phosphorylation in Src family Kinase Activation and Neurite Formation

Abstract: There are two developmentally regulated alternatively spliced forms of Disabled-1 (Dab1) in the chick retina: an early form (Dab1-E) expressed in retinal precursor cells and a late form (Dab1-L) expressed in neuronal cells. The main difference between these two isoforms is the absence of two Src family kinase (SFK) recognition sites in Dab1-E. Both forms retain two Abl/Crk/Nck recognition sites implicated in the recruitment of SH2 domain-containing signaling proteins. One of the Dab1-L-specific SFK recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…1). In previous reports, we have shown that exogenous GFP-Dab1-L but not GFPDab1-E is robustly tyrosine phosphorylated in transfected retinal cells (41)(42).…”
Section: Dab1-e Is Not Tyrosine Phosphorylated and Does Not Interact mentioning
confidence: 72%
“…1). In previous reports, we have shown that exogenous GFP-Dab1-L but not GFPDab1-E is robustly tyrosine phosphorylated in transfected retinal cells (41)(42).…”
Section: Dab1-e Is Not Tyrosine Phosphorylated and Does Not Interact mentioning
confidence: 72%
“…Our finding that the ab mutant is virtually inactive implies that the a site may take over if the b site is unavailable. Also, all four phosphorylation sites are required for overexpressed Dab1 to induce the differentiation of zebrafish retinal precursor cells (26). However, phosphorylation of the a site in neurons has not yet been confirmed.…”
Section: Resultsmentioning
confidence: 97%
“…Primary retinal cultures were prepared from embryonic day (ED) 5 or ED10 chick retinas dissociated with trypsin as previously described [8]. The treatments and transfections were carried out 24 h after plating.…”
Section: Cell Culture Drug Treatment and Dna Transfectionmentioning
confidence: 99%
“…The N-terminal domain is followed by a tyrosine-rich region, which consists of five highly-conserved tyrosine (Y) residues (Y185, Y198, Y200, Y220 and Y232) corresponding to two consensus Src family kinase (SFK) recognition sites (Y185 and Y198/Y200) and two consensus Abl recognition sites (Y220 and Y232) [5]. At least three of the four tyrosine phosphorylation sites (Y198, Y220 and Y232) are phosphorylated by SFKs and/or involved in the activation of SFKs in cultured neurons upon Reelin stimulation [6][7][8]. Tyrosine phosphorylation of Dab1 is essential for Reelin signaling, as mice expressing Dab1 with substitutions at these five tyrosine residues have neuronal cell positioning defects similar to those observed in Reelin-deficient (reeler) and Dab1−/− mice [9].…”
Section: Introductionmentioning
confidence: 99%